Bank lending rates and the remuneration for risk: Evidence from portfolio and loan level data - Agha Durrani; Julian Metzler; Nektarios Michail; Johannes-Gabriel Werner (European Central Bank (ECB), 2022)
We employ interest rates and expected loss probabilities from the 2021 EBA Stress Test dataset and euro area credit registries to examine whether the risk-return relationship holds in banking. After controlling for bank, loan, and debtor characteristics as well as macroeconomic conditions, results indicate that a risk-return relationship in bank lending is present but varies significantly across and within borrower segments. While bank lending rates appear to be quite responsive to risks towards households, results suggest that banks only significantly increase interest rates towards non-financial corporations that reside in the riskiest quantiles of the distribution. This potentially implies the presence of a cross-subsidization effect of credit risk.
Keywords: E51; E52; E58; 330; risk-return; credit register; banking; loans; interest rates